The relationship between body-mass index and overall survival in non-small cell lung cancer by sex, smoking status, and race: a pooled analysis of 20,937 International lung cancer consortium (ILCCO) patients - Jiang, Mei; Fares, Aline F.; Shepshelovich, Daniel; Yang, Ping; Christiani, David; Zhang, Jie; Shiraishi, Kouya; Ryan, Brid M.; Chen, Chu; Schwartz, Ann G.; Tardon, Adonina; Shete, Sanjay; et al. (Lung cancer, 2021)
Introduction - The relationship between Body-Mass-Index (BMI) and lung cancer prognosis is heterogeneous. We evaluated the impact of sex, smoking and race on the relationship between BMI and overall survival (OS) in non-small-cell-lung-cancer (NSCLC). - Methods - Data from 16 individual ILCCO studies were pooled to assess interactions between BMI and the following factors on OS: self-reported race, smoking status and sex, using Cox models (adjusted hazard ratios; aHR) with interaction terms and adjusted penalized smoothing spline plots in stratified analyses. - Results - Among 20,937 NSCLC patients with BMI values, females=47 %; never-smokers=14 %; White-patients=76 %. BMI showed differential survival according to race whereby compared to normal-BMI patients, being underweight was associated with poor survival among white patients (OS, aHR=1.66) but not among black patients (aHR=1.06; pinteraction=0.02). Comparing overweight/obese to normal weight patients, Black NSCLC patients who were overweight/obese also had relatively better OS (pinteraction=0.06) when compared to White-patients. BMI was least associated with survival in Asian-patients and never-smokers. The outcomes of female ever-smokers at the extremes of BMI were associated with worse outcomes in both the underweight (pinteraction<0.001) and obese categories (pinteraction=0.004) relative to the normal-BMI category, when compared to male ever-smokers. - Conclusion - Underweight and obese female ever-smokers were associated with worse outcomes in White-patients. These BMI associations were not observed in Asian-patients and never-smokers. Black-patients had more favorable outcomes in the extremes of BMI when compared to White-patients. Body composition in Black-patients, and NSCLC subtypes more commonly seen in Asian-patients and never-smokers, may account for differences in these BMI-OS relationships.
Available online 4 December 2020
Gesehen am 13.04.2021